Representasi Profesi Wartawan Dalam Lagu “Kisah Seorang Wartawan” Karya Jamal Abdillah - Zannuba Chavilla Andjari; M Amin Sihabudin; Ahmad Harun Yahya (Social Science and Contemporary Issues Journal, 2024)
The journalist profession has an important role in the process of delivering messages to the wider community. Representation of this profession is not only limited to writing, it can also be found in a song work. The Story of a Journalist is a song composed by Jamal Abdillah that describes the experiences and challenges faced by a journalist. This study aims to clarify how the representation of the journalist profession and the content of the message in the song "The Story of a Journalist" by Jamal Abdillah. This research includes qualitative descriptive research. Data collection techniques are carried out with documentation techniques because the object is in the form of songs. While the analysis technique with two-stage meaning based on Roland Barthes' Semiotic Theory. The lyrics of this song are in Malaysian Malay, so researchers translate it into Indonesian first. In the first stage, researchers interpret song lyrics by revealing the meaning of connotations, denotations, and myths. Furthermore, conduct in-depth research with the real journalist profession.  This research resulted in the conclusion that: 1) Jamal Abdillah described a journalist clearly based on the actual professional duties of journalists in the lyrics of his Malaysian Malay song entitled "The Story of a Journalist". 2) Jamal Abdillah tells the story of a journalist's career journey that was not easy and full of challenges. From the first verse to the fourth, he elaborates the story of a journalist continuously. Starting from the first verse that describes the task of a journalist who works without time to find news that can change people's mindsets. The second stanza represents the profession of a journalist who works based on a journalistic code of ethics and must be prepared to face obstacles in finding news that will later be published in cyberspace. Then in the third verse, the researcher gets the results of the analysis that the realm of a journalist in finding news is no longer limited to challenges. With the invisible movement of journalists' work, it makes him sometimes praised but sometimes forgotten. Finally, the analysis of the fourth stanza represents the noble intention of a journalist in boosting information in various aspects of people's lives, one of which is the art world for artists. Not only that, Jamal Abdillah also saw the number of journalists whose lives were not protected so that not a small number of journalists died while on duty. The message and deep meaning in each verse of this song invites listeners to appreciate the steps of a journalist, where people just enjoy the treat of published news without seeing the movement when the journalist is on duty.